1990
DOI: 10.1177/096032719002200103
|View full text |Cite
|
Sign up to set email alerts
|

Photopic luminance does not always predict perceived room brightness

Abstract: The perception of room brightness over photopic luminances ranging from 30 cd/m2 to 67 cd/m2 was judged by 12 subjects in an almost uniformly white experimental chamber. Two different illuminants were compared which had different spectral compositions, but were color matched. Brightness judgements were often opposite to large differences in photopic luminance. These results are inconsistent with models of brightness perception that depend solely on cone receptors. At the luminance levels considered here subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 8 publications
2
75
0
Order By: Relevance
“…One study 30 associates the scotopic to photopic (S/P) ratio with spatial brightness, and purposefully presented two lighting conditions of near-identical chromaticity (and hence equal cone excitation) but different S/P ratio. The results suggested that lighting of higher S/P ratio appears brighter.…”
Section: Lamp Spd and Brightnessmentioning
confidence: 99%
See 1 more Smart Citation
“…One study 30 associates the scotopic to photopic (S/P) ratio with spatial brightness, and purposefully presented two lighting conditions of near-identical chromaticity (and hence equal cone excitation) but different S/P ratio. The results suggested that lighting of higher S/P ratio appears brighter.…”
Section: Lamp Spd and Brightnessmentioning
confidence: 99%
“…This raises a question as to whether the experimental design matters. For example, is discrimination of the brighter scene from sequential evaluation of lighting from two different light sources 30 comparable with category rating of their brightness when evaluated separately? 44 These two particular studies disagree in their conclusions as to whether SPD affects brightness and one possible explanation is the differences in the particular procedures employed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the differences between these models [16][17][18][19][20][21][22][23][26][27][28] , it is important to appreciate that none of them predict any effect of SPD in photopic conditions, yet it is well established that SPD does influence brightness perception in photopic conditions [30][31][32][33][34] . Indeed, there are empirical models for predicting brightness under different light sources in photopic conditions based on this effect 32,[34][35][36][37] .…”
Section: Models Of Mesopic Visionmentioning
confidence: 99%
“…Indeed, there are empirical models for predicting brightness under different light sources in photopic conditions based on this effect 32,[34][35][36][37] . This does not mean that the mesopic models are incorrect.…”
Section: Models Of Mesopic Visionmentioning
confidence: 99%
“…Indeed, photopic sensitivity is still routinely measured by constricting the test subject's field of view to a maximum of 2 degrees (less than 0.1% of the normal field of view of the human eye) in order to exploit the absence of rod photoreceptors in the central portion of the retina, thus isolating and measuring only the cone responses (Berman et al, 1990(Berman et al, , 1996Bouma, 1962). As a result of these longstanding methods, current lighting industry recommendations for indoor illumination and room brightness (and the calibration of lightmeasuring devices) have been based solely upon the sensitivity of only one of the two key photoreceptor cell types: the cone receptors (responsible only for photopic sensitivity).…”
Section: Brightness and Glare Levels Of Office And Classroom Lightingmentioning
confidence: 99%